The Profile of the Participants of the Lectures Cycle GESPORTE - Alexandre Lima de Araújo Ribeiro; Francielly Martins Prado; Caio Henrique Quemel Siqueira; Pedro Victor Nogueira de Souza; Paulo Henrique Azevêdo (Universidade Salgado de Oliveira, 2021)
This study aimed to characterize the profile of participant in the Technical Lectures of the Lectures Cycle GESPORTE. Thus, it is a descriptive research, which used a questionnaire as a data collection instrument, this questionnaire contained closed and open questions. Of the 967 participants in the technical lectures analyzed, 335 responded to the data collection instrument that contained questions about gender variables; age; study level; course; activity that exerts; personal monthly income; aspects of the event (access to the event venue; parking; auditorium; seating; restrooms; conducting the event (ceremonial); punctuality of the event; signage and information; importance of the event (theme); quality of the speakers). The results show that 60.6 are men; 85.7% are up to 24 years old; 64.6 has a monthly income of up to R $ 1,000.00 (one thousand reais); 90.4% are undergraduate students; and 88% are studying Physical Education. Therefore, the participants in the GESPORTE Lectures Cycle are men up to 24 years old, undergraduate students in Physical Education, with a monthly income of up to R $ 1,000.00 (one thousand reais).